Determinants of Indonesia’s National Income: An Auto-Regressive Distributed Lag Analysis - Prihartini Budi Astuti; Nur Khasanah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2020)
At the end of 2019, most countries experienced an economic slowdown due to a trade war between the United States and China. According to macroeconomic theory, aggregate demand is one of the factors that influence economic growth. This study aims to add the debate and fill the gap by studying the relationship between aggregate demand and economic growth in the case of Indonesia. Using an Auto-Regressive Distributed Lag analysis, the results indicate that in the long-run, household consumption and investment had a positive effect on Indonesia's national income in 2010-2019. It means that the government must continue to make policies to maintain the purchasing power of Indonesian consumers, so that public consumption remains high, and maintaining the investment climate to be more conducive. On the other hand, government expenditure and net exports variables have no impact on Indonesia's national income in 2010-2019.JEL Classification: E01, E12, O47How to Cite:Astuti, P. B., & Khasanah, N. (2020). Determinants of Indonesia’s National Income: An Auto-Regressive Distributed Lag Analysis. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 207-218. https://doi.org/10.15408/sjie.v9i2.14469.